A Review of Taila Varga (Edible Vegetable Oils) According to Bruhat Trayi (International Journal of Ayurveda and Pharma Research, 2023)
Vegetable oils have been used for many centuries in traditional Ayurvedic medicine in India and in Chinese medicine for their therapeutic properties. The purpose of this article is to inform readers about the characteristics of edible oil as described in Ayurveda, with particular emphasis on Charak Samhita, Sushruta Samhita, and Ashtanga Hridaya. Literature about nutrition and dietetics was studied in books, journals, and research engines. The main components of vegetable oils are sesame, coconut, groundnut, sunflower, soybean, palm, safflower, and mustard oils. Many other oils used as essential oils or for medicinal purposes. In addition, many oils can be used as functional food.